Predisposing Factors of the Head of Family with Bali ID Card to Join the National Health Insurance (JKN) Program: A Qualitative Study in Health Centre I North Denpasar - Cokorda Istri Mita Pemayun; Pande Putu Januraga; Ni Made Ayu Sri Ratna Sudewi (Public Health and Preventive Medicine Archive, 2016)
Background and purpose: Since 2010, The Government of Bali has implemented local health financing (JKBM) to provide free health care services for Bali’s citizen, meanwhile, since 2014 the central government has started to implement the National Health Insurance program (JKN) based on participant’s monthly contribution. Although JKBM still available until 2017, there is a phenomenon of people who have Bali ID card turned into JKN. This article explores predisposing factors of the family head with Bali ID cards so that they switched into JKN scheme with relatively the same medical services and facilities. Methods: Interviews were conducted with purposively selected participants through the exit interview by using in-depth interview guide to 13 participants of JKN, three region leaders, three participants of JKBM and one public health central officer. Data were analyzed thematically and presented in a narrative form. Results: The interviews showed that participants who switched to JKN are concerned with sustainability and the quality of services in JKBM program. Participants perceived high vulnerability to disease from previous experience using JKBM program. Conclusion: Based on the consideration of participants to switch the membership becoming independent JKN Class III, it can be recommended improve the cooperation among stakeholders to enhance the socialization of JKN especially through the involvement of listed participants who already used JKN program.